Crisis in the valuation, emotional labor and occupational burnout among teachers of religion - Bogusława Lachowska; Karol Starczewski (Nofer Institute of Occupational Medicine, 2015)
Background: This article presents an analysis of the relationship between the crisis of values and in the valuation, the strategy of emotional labor, and occupational burnout in the group of lay teachers of religion. In addition, the role of emotional labor as a mediator of the relationship between the crisis of values and burnout was analyzed. Three strategies of emotional labor were considered in the study: surface acting, deep acting, and expression of naturally felt emotions. Material and methods: The study was conducted in a group of 169 lay teachers of religion (males - 24%, females - 76%), using the Questionnaire for Investigating Crisis in Valuation developed by Oleś, the Maslach Burnout Inventory, and the Emotional Labour Scale developed by Diefendorff, Croyle and Gosserand. Results: The crisis of values and in the valuation is an important factor responsible for occupational burnout in the group of lay teachers of religion. Surface acting and expression of naturally felt emotions mediate the relationship between crisis in the valuation and emotional exhaustion, depersonalization and lack of personal accomplishment. Surface acting increases, while the expression of naturally felt emotions decreases occupational burnout. Deep acting is not related with occupational burnout. Conclusions: It is justified to seek factors favoring the expression of naturally felt emotions, and also those reducing surface acting. Med Pr 2015;66(5):687-700